2006
DOI: 10.1249/01.mss.0000228937.86539.95
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Physical Activity in Canadian Adults with Diabetes

Abstract: Many of our results for both diabetes types are consistent with findings from other limited research in this domain. Contrary to previous research, however, a significant negative relationship was reported between body mass index and PA for the type 2 group. In addition, perceived disability was negatively associated with PA, which, to date, has not been reported in the literature with type 2 individuals. Research and practice related to physical activity promotion for this population should take into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
190
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(203 citation statements)
references
References 19 publications
8
190
4
1
Order By: Relevance
“…Canadian data from Plotnikoff et al (2006) found younger age, being male, higher education, higher income, and lower BMI to be positively associated with MVPA among adults with type 2 diabetes. 13 Our results add to the discussion showing that female sex and increasing BMI are negatively associated with MVPA. We found a negative association between not reporting income and PA. Uniquely, we also found that those who were unemployed were more active relative to those who reported being employed.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Canadian data from Plotnikoff et al (2006) found younger age, being male, higher education, higher income, and lower BMI to be positively associated with MVPA among adults with type 2 diabetes. 13 Our results add to the discussion showing that female sex and increasing BMI are negatively associated with MVPA. We found a negative association between not reporting income and PA. Uniquely, we also found that those who were unemployed were more active relative to those who reported being employed.…”
Section: Discussionsupporting
confidence: 71%
“…Among our sample, 90% did not meet physical activity guidelines. This figure is higher than previous Canadian data from Plotnikoff et al (2006), 13 who reported that among a sample of 1614 adults with type 2 diabetes, 72% were not achieving 150 minutes/week of MVPA based on data collected using a self-reported tool (Godin Leisure-Time Exercise Questionnaire-GLTQ). 25 The disparate results are not surprising given the GLTQ has been shown to have low-to-moderate agreement with objective measures of PA (e.g., CALTRAC accelerometer).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Given that, and despite frequent physicians recommendation of a physically active lifestyle, patient adherence is still low. It needs to be strengthened by the investigation of factors influencing adherence to physical activity, which can possibly lead to measures for improvement exercise programs effectiveness (28).…”
Section: Introductionmentioning
confidence: 99%
“…12 However, a recent population-based study found that only 28 % of people with type 2 diabetes achieve these recommendations. 13 The majority of people with type 2 diabetes have low PA. As a proof of this statement, a US study of 23,263 adults found that 39 % of adults with type 2 diabetes were physically active versus 58 % of adults without type 2 diabetes.…”
mentioning
confidence: 99%